2014
DOI: 10.1016/j.pjnns.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation is compromised in ischaemic stroke of undetermined aetiology only in the non-affected hemisphere

Abstract: During the first days of ischaemic stroke of undetermined aetiology, dynamic cerebral autoregulation is compromised in the non-affected hemisphere, but not in the hemisphere with ischaemic lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Only two studies demonstrated a higher gain on the affected 23,40 and unaffected hemispheres 23 in AIS patients. However, on pooled analyses, gain was significantly lower (signalling better autoregulation) in AIS compared to control.…”
Section: Gainmentioning
confidence: 96%
See 3 more Smart Citations
“…Only two studies demonstrated a higher gain on the affected 23,40 and unaffected hemispheres 23 in AIS patients. However, on pooled analyses, gain was significantly lower (signalling better autoregulation) in AIS compared to control.…”
Section: Gainmentioning
confidence: 96%
“…25,30,33,50 Eleven studies presented the modified Rankin Scale (mRS). 13, 24, 27, 29, 32, 35-38, 43, 46 Moreover, the majority of participants were recruited within 6 to 72 hours from stroke onset, 2, 12, 13, 24-27, 29, 34-40, 42, 43, 45-47, 49, 51 including within 48 hours (n = 8), 2, 25, 34-36, 39, 47, 49 five studies assessed dCA at 72 hours, 24,29,40,45,51 twenty-four hours were studied in four studies, 37,42,43,46 three studies examined dCA between 30 to 37 hours, 12,13,38 dCA was assessed at 6 hours (n = 2), 26,27 one study assessed between onset to 16 days, 52 other three studies recruited participants after first week of stroke onset 32,33,48 and one study examined recovery at 6 months. 49 The location of the lesion was identified in the MCA (n = 13), 23, 26-28, 33-37, 40, 41, 49, 51 posterior cerebral artery (n = 3), 31,32,49 and anterior cerebral artery territories (n = 3), 2, 25, 52 though eight studies did not specify the precise localization of the lesion.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies [21,22,23,24], we measured forehead tHb, HbO 2 , and deoxyHb within 72 h (first measurement) and 7–10 days (second measurement) after AIS onset. After placing probes on the forehead, the participant laid on his/her back.…”
Section: Methodsmentioning
confidence: 99%